Importance and place of Bahodir Jalolov's work in the development of Uzbekistan's majestic color image - Mamatkulov Rashidbek Ravshanbekovich (Zien Journals, 2021)
The independence of Uzbekistan laid the foundation for the development of national fine arts. During this period, the fine arts of painting, sculpture, graphics, its many genres, the free creative activities of artists and sculptors became widespread. The Uzbek people are a people who truly appreciate art. This article discusses the importance and place of Bahodir Jalolov's work in the development of the majestic color image of Uzbekistan, the unique artistic path created by this great artist, as well as the essence of dozens of paintings in museums. considerations are made.
Keywords: Bahodir Jalolov; creativity; artist; brush